1985
DOI: 10.1021/bi00345a021
|View full text |Cite
|
Sign up to set email alerts
|

Cryoenzymology of Bacillus cereus .beta.-lactamase II

Abstract: The effects of cryosolvents and subzero temperatures on the metalloenzyme beta-lactamase II from Bacillus cereus have been investigated. Preliminary experiments led to the selection of suitable systems for the study of beta-lactamase II catalysis at low temperatures, namely, cobalt(II) beta-lactamase II hydrolysis of benzylpenicillin in 60% (v/v) ethylene glycol and zinc beta-lactamase II hydrolysis of the chromophoric cephalosporin nitrocefin in 60% (v/v) methanol. Progress curves for the hydrolysis of benzyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
118
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(131 citation statements)
references
References 40 publications
13
118
0
Order By: Relevance
“…The affinity for Co(II) is thus two orders of magnitude weaker than for Zn(II) because of the lower value for the association rate k on,1 for Co(II). The spectral features obtained at a [Co(II)]/[enzyme] ratio of 1 are identical to those described earlier (23). Increasing the [Co(II)]/[enzyme] ratio above 1 results in an additional charge transfer band at 383 nm.…”
Section: Table II Results Of Theoretical Exafs Data Analysis For Wildsupporting
confidence: 81%
See 1 more Smart Citation
“…The affinity for Co(II) is thus two orders of magnitude weaker than for Zn(II) because of the lower value for the association rate k on,1 for Co(II). The spectral features obtained at a [Co(II)]/[enzyme] ratio of 1 are identical to those described earlier (23). Increasing the [Co(II)]/[enzyme] ratio above 1 results in an additional charge transfer band at 383 nm.…”
Section: Table II Results Of Theoretical Exafs Data Analysis For Wildsupporting
confidence: 81%
“…The same spectral changes as described here were obtained in 15 mM sodium cacodylate, pH 7.0 (data not shown). Earlier studies were performed in succinate buffer at pH 6.3 (24) or in a cryosolvent containing 60% ethylene glycol in 80 mM sodium cacodylate, pH 6.4 (glass electrode reading in aqueous-organic solvent) (23). It might be assumed that solvent composition, the presence of succinate, and/or the lower pH are responsible for the different spectroscopic behavior.…”
Section: Table II Results Of Theoretical Exafs Data Analysis For Wildmentioning
confidence: 99%
“…Put together, these results are consistent with a red shift of the substrate spectrum upon binding to the enzyme. An intermediate in nitrocefin hydrolysis by BcII with a red shifted absorption maximum was already reported by Bicknell and Waley in cryosolvents at sub zero temperatures 14 , who also reported that spectral shifts of this kind occur to nitrocefin when lowering the solvent polarity. Subclass B1 metallo-β-lactamases have a flexible loop which closes upon substrate binding [15][16][17] .…”
Section: Kinetic Measurement Of the Hydrolytic Reactionsupporting
confidence: 61%
“…It is likely that a replacement of water by sulfur in the H-site results in the observed changes (compare Ref. 29). The appearance of two additional bands at 310 and 375 nm can be attributed to sulfurcobalt ligand-to-metal charge transfer due to binding of the captopril sulfur.…”
Section: Discussionmentioning
confidence: 82%